Jack eaudiobook A novel. - Robinson, Marilynne (Gilead, 2020)
" Robinson's slow prose is the star here, and narrator Adam Verner gives great depth of emotion to Jack's raw suffering and ethical dilemmas...Come for the love story; stay for a couple who learn to find the beauty in broken humanity, and what grace can look like for those who love each other." — Booklist This program includes a bonus conversation with the author. Marilynne Robinson, winner of the Pulitzer Prize and the National Humanities Medal, returns to the world of Gilead with Jack, the latest novel in one of the great works of contemporary American fiction Marilynne Robinson's mythical world of Gilead, Iowa—the setting of her novels Gilead , Home , and Lila , and now Jack —and its beloved characters have illuminated and interrogated the complexities of American history, the power of our emotions, and the wonders of a sacred world. Jack is Robinson's fourth novel in this now-classic series. In it, Robinson tells the story of John Ames Boughton, the prodigal son of Gilead's Presbyterian minister, and his romance with Della Miles, a high school teacher who is also the child of a preacher. Their deeply felt, tormented, star-crossed interracial romance resonates with all the paradoxes of American life, then and now. Robinson's Gilead novels, which have won one Pulitzer Prize and two National Book Critics Circle Awards, are a vital contribution to contemporary American literature and a revelation of our national character and humanity. A Macmillan Audio production from Farrar, Straus and Giroux